BFLA Spanish-English Mexican American bilinguals. Issue 1 (2nd January 2019) - Nalls, Irdawati Bay
ABSTRACT: The author looks at bilingual first language acquisition Spanish-English Mexican American bilinguals across an elementary school in Colorado. Based on classroom observations, and small group and one-on-one interviews with student participants, their teachers, and immediate family members, these bilinguals reveal how their identity is compromised as they survive in predominantly English-speaking settings. Their struggles, as they acculturate in America through their attempt to blend heritage and societal languages, and cultural practices, are revealed in the intimate sharing of counternarratives. Their suppressed voices bring forth a story about identity and the need to reposition the marginalized by giving recognition to abilities.